Achieving high strength-ductility in pure copper by cold rolling and submerged friction stir processing (SFSP). (July 2021) - Mazaheri, Hoora; Aval, Hamed Jamshidi; Jamaati, Roohollah
Abstract: In this research, the combined effect of pre-rolling and submerged friction stir processing (SFSP) on the microstructure, hardness, and tensile behavior of commercially pure copper were evaluated. Several voids and cavities were observed in the stirred zone of 0 %–400, 60 %–400, 60 %–600, and 0 %–800 samples, and the defect-free copper could be achieved under a narrow process window. The microstructures revealed that a significant decrement in grain size occurred in the stirred zone of the SFSP-processed coppers due to the occurrence of dynamic recrystallization (DRX) and water cooling conditions. The pre-rolling led to decreasing the grain size after the SFSP owing to providing more nucleation sites for recrystallization. In the 60 %–800 sample, despite the increase in heat-input by increasing the rotational speed, due to the pre-strain, the average hardness was about 5 HV higher than the 0 %–600 sample (92.2 HV vs. 87.1 HV). In the case of the 0% sample, by conducting the SFSP, the yield and ultimate tensile strengths (YS and UTS) increased to 215 and 277 MPa, respectively, due to the lower grain size of the 0 %–600 sample as compared to the 0% sample (4.5 μm vs 17.9 μm). On the other hand, in the 60 %–800 sample, the YS and UTS reduced to 307 MPa as compared to the 60 % sample owing to the transition of the strengthening mechanism from strain hardening to grain refinement. The fractured surfaces of all samples exhibited a ductile manner. However, after the SFSP, the size and depth of dimples were reduced due to the finer grain size.